Averaging is Key to Build and Use a Multidimensional Vulnerability Index - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2022)
In the general presentation of the criteria that the MVI should meet, we emphasized the importance of the way by which the three dimensions of the MVI are averaged in a single index and the need to limit the substitutability between them, so that the specific vulnerability of each country can be fairly reflected. [...]
Keywords: 330